(untitled) (Journal of Parents and Teachers, 2025)
The article discusses a drug prevention program aimed at providing educational resources in schools. It also presents the idea that the word "no" pertains to more areas than just drugs. Additionally, a series of final supplements are developed, enumerating skills teachings, the groups that emerge, and evaluation instruments.